(untitled) (American Journal of Arts and Human Science, 2024)
The study investigates the perceptions of Moroccan secondary school teachers regarding the academic performance of science and literary stream students aged 16 to 18. Through a combination of mail surveys, unstructured interviews with English teachers, and discourse analysis, the research identifies that English as the second foreign language in Moroccan schools influences the perceived advantages of science stream students over their literary counterparts. The findings align with a previous study and suggest that science students often pursue literary studies at Moroccan universities post-baccalaureate. The research delves into the distinctive characteristics of science stream students and proposes recommendations for governmental and ministerial reforms in the Moroccan educational system. The study underscores the historical incorporation of English in the Moroccan educational system since 1956 and highlights recent developments, such as the expansion of English language teaching to middle schools. It emphasises the impact of English language learning on students’ future orientations and tendencies in higher education. Ultimately, the study aims to draw attention to English teachers’ perceptions to facilitate positive changes in the Moroccan educational system, urging the education ministry and relevant authorities to consider reforms.